The 4Rs of harmonious living - Abd Razak, Dzulkifli (2005)
EIDULMUBARAK, or better known locally as Hari Raya Aidilfitri, the festival to end the holy month of Ramadan, will be celebrated this week. As we approach the festivities, we are reminded of the two Singaporean bloggers who posted on the Internet what the island's deputy public prosecutor called "highly inflammatory and insulting" remarks. Maybe it is appropriate to revisit the incident and see what lessons can be learnt from this unfortunate but important episode. The duo had admitted to making the seditious remarks on the Internet in response to a letter in The Straits Times (June 14) where a woman with a Muslimsounding name wanted to know whether uncaged pets (not just dogs) are allowed in taxis. In fairness, her concern was more about cleanliness.